Machine Times - Brouwer, Joke (Rotterdam V2_Publishing, 2000)
What is "the Now" wrapped in technological immersion? Is the depth of the moment, only something to remember or are we continually confronted by non-stop moments in real-time?In contrast to extensive time, the time of duration and continuity, technology provokes intensive time, according to Virilio - intensive time being the technological acceleration of moments which we are unable to grasp. Whereas the millisecond may be child's play to the computer, the brain takes about 0.3 seconds to find synchronicity in the experience of time and space. As the intensive time of the computer drastically eliminates the space continuum, all focus moves to purely time-based media, producing high-speed machine times. How does the mind relate to these machine times? How does extensive time collide and perhaps intertwine into the accelerated pace of technology? Must we shift gears to matrix-minded speeds just to keep up? The DEAF_00 book may prove the impulse ... with texts by Francisco Varela, Detlef Linke, Mark Taylor, Eugene Thacker, Douwe Draaisma, Atau Tanaka, Kodwo Eshun, Robert Levine, Peter Weibel and Æ.Also linked to the symposium, the book gives catalogue information on the exhibition and other presentations at the festival ... coming to grips with the synchronization of time-based information, perhaps it is time to speed up your sensory data input?
Essays and Interviews -- Introduction -- Francisco Varela: The Deep Now -- Detlef Linke: The Rhythms of Happiness -- Mark C. Taylor: We are the incarnation of complex Worldwide Webs -- Eugene Thacker: Regenerative Medicine: We Can Regrow It For You Wholesale -- Douwe Draaisma: The Clockwork of the Mind -- Atau Tanaka: Speed of Sound -- Kodwo Eshun: Visions of rhythm in the kinematic pneumacosm of Hype Williams -- Robert Levine: Time Talks, with an Accent -- Peter Weibel: Chronocracy -- Æ: S8P Antennas, Transmission -- Andrej Ujica: Out of the Present -- Claudia Kölgen: Sitting -- Martin Reinhard/Virgil Widrich: tx-transform -- Mari Soppela: Heimola -- Akisugu Maebayashi: Sonic Interface -- John F. Simon jr.: Every IconMarnix de Nijs: Panoramic Acceleration -- Eike: X=X+1 (INCREmental) -- Christian Kessler: Transverser -- IBW: Yes, we have no Norit -- Ron Kuivila: Twilight of the Second Hand -- Dieter Jung: Light Mills -- Perry Hoberman: Timetable -- Woody Vasulka: Time/Energy Object and its Building Element, the Waveform -- Atau Tanaka/Kasper Toeplitz: Global String -- Gerald van der Kaap: 12th of Never -- Ana Giron: Artificial Time -- Gregory Barsamian: The Trap -- ART+COM: Ride the Byte -- Ikuo Nakamura: The Mirror